Pharmacognosy and Analytical Profile of Bhunimbadi Churna: A Polyherbal Formulation - Pratik Sharma; Anand B. More; R Galib; Shalini Rai; Anjali Upadhyay (Wolters Kluwer Medknow Publications, 2024)
Background: Charak Samhita, an ancient Ayurvedic text, offers a vast repository of effective polyherbal formulations for treating various diseases. Ensuring the standardization and authentication of these compound formulations is crucial for quality control and enhancing their therapeutic efficacy. Establishing reliable data to set standard parameters is essential for verifying the genuineness of individual formulations and drugs as a whole. Aims and Objectives: The primary aim of this study is to evaluate and assess Bhunimbadi Churna, a classical formulation mentioned in the Grahanidosha Chikitsa Adhyaya of Charak Samhita, known for its multiple therapeutic indications. The objectives include conducting a comprehensive pharmacognostical and pharmacological assessment of the formulation to establish standard parameters for quality control. Materials and Methods: The study involved a detailed examination of Bhunimbadi Churna using standard scientific protocols. The assessment included organoleptic characteristics, physico chemical parameters, physical characteristics of the powder (Churna), preliminary phytochemical analysis, and high performance thin layer chromatography (HPTLC) analysis. Results: On performing the experiments for three consecutive readings, loss on drying was found to be 7.66 ± 0.21, pH was 5.53 ± 0.19, total ash value of powder was found to be 6.64 ± 0.20 w/w, and acid insoluble ash was found to be 0.52 ± 0.11 w/w. These parameters provide a reliable framework for assessing the quality and authenticity of the formulation. Conclusion: The findings of this study offer valuable tools for regulatory authorities, scientific organizations, and manufacturers to develop standardized formulations of Bhunimbadi Churna. The reproducible parameters established in this study can assist in ensuring the quality and efficacy of this classical Ayurvedic formulation.